The Effect of Different Concentrations of Rice Washing Water as a Growth Regulator on the Quality of Cuttings of Jasmine Plants - Ida Rona Ully Septiyanti Sitohang; Antar Sofyan; Ronny Mulyawan (Formosa Journal of Science and Technology, 2023)
Jasmine plant is a flowering plant that has many benefits. One of them is the basic ingredient of essential oils. This study aims to determine the effect of soaking ZPT in rice washing water and the dosage of rice washing water on the quality of jasmine cuttings. This study used a one-factor Completely Randomized Design (CRD) method with six concentrations of rice washing water, namely: P1 (ZPT Root Up 5%), P2 (Rice Washing Water 50%), P3 (Fermentation Rice Washing Water 40%), P4 (45% Rice Wash Water Fermentation), P5 (50% Rice Wash Water Fermentation), P6 (55% Rice Wash Water Fermentation), with 4 replicates obtained 24 experimental units. The parameters observed were the time of emergence of shoots, the percentage of the number of shoots, shoot length, number of roots and root length. The results obtained showed that the best concentration of immersion using rice washing water on the quality of jasmine cuttings was the fermentation treatment of rice washing water 40% and 45%.